2007
DOI: 10.5012/bkcs.2007.28.6.929
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Acetylcholinesterase-Based Detection Kit for the Determination of Organophosphorus and Carbamate Pesticide Residues in Agricultural Samples

Abstract: The objective of this study was to develop a rapid, simple, and qualitative acetylcholinesterase (AChE)-detection kit, based on a modification of the Ellman and ELISA methods, for the detection of organophosphorus (OP) and carbamate (CB) pesticide. The developed kits were used to screen a large number of agricultural samples (spiked and real) for OP and CB pesticide residues. AChE was extracted from the heads of honeybees (Apis mellifera L.) using Triton X-100, and was purified through 3 steps: diethylaminoeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 31 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Thus, other high throughput screening techniques for more rapid detection of pesticide residues have been investigated. Kim et al (2007) developed an acetylcholinesterase detection kit, based on a modification of Ellman and ELISA methods for the detection of organophosphorus (0.50 to 2.50 ppm detection limit) and carbamate (0.50 to 4.75 ppm detection limit) pesticides in agricultural samples. The use of this kit resulted in substantial decrease in cost and time compared to antibody-based immunoassays that require expensive equipment.…”
mentioning
confidence: 99%
“…Thus, other high throughput screening techniques for more rapid detection of pesticide residues have been investigated. Kim et al (2007) developed an acetylcholinesterase detection kit, based on a modification of Ellman and ELISA methods for the detection of organophosphorus (0.50 to 2.50 ppm detection limit) and carbamate (0.50 to 4.75 ppm detection limit) pesticides in agricultural samples. The use of this kit resulted in substantial decrease in cost and time compared to antibody-based immunoassays that require expensive equipment.…”
mentioning
confidence: 99%
“…Since this study demonstrated that the LOD for OPs and CMs was between 0.002 and 0.508 ppm, it is comparable to the LOD of a paper-based acetylcholinesterase inhibition assay using commercial acetylcholinesterase for the detection of OPs, which was between 0.003 and 0.600 ppm [31]. The results were superior to the qualitative acetylcholinesterase detection kit based on a modi cation of the Ellman and ELISA methods, using honeybee (Apis mellifera L.) heads as the source of ChE with a LOD range of 0.50-4.80 ppm [32]. Furthermore, the newly developed smartphone-based colorimetric sensor technique demonstrated that the low LOD of a method for all pesticides was less than 1.5 x 10(-7) M, indicating greater sensitivity than the U.S.…”
Section: Discussionmentioning
confidence: 89%
“…The study established that the LODs for OPs and CMs ranged from 0.036 to 0.086 ppm, which is within the range of the LODs for a paper-based AChE inhibition assay using commercial AChE to detect OPs, reported between 0.003 and 0.600 ppm [ 30 ], and our previous colorimetric method, which used the same cricket cholinesterase (LOD 0.002–0.508 ppm) [ 23 ]. The results were superior to those of the qualitative acetylcholinesterase detection kit, which was modified from the Ellman and ELISA methods and used honeybee heads as the source of ChE, exhibiting a LOD range of 0.50–4.80 ppm [ 31 ]. Furthermore, the potentiometric enzyme inhibition-based OP biosensor technique demonstrated a LOD of 0.038 μM and a linearity range of 50 × 10 3 to 2.5 × 10 3 μM for trichlorfon detection, with an incubation time of 15 min and good storage stability of 30 days [ 32 ].…”
Section: Discussionmentioning
confidence: 99%